Teacher beliefs and attitudes towards children’s’ risk-taking behavior in the outdoor setting - Imaz Recondo, Oihana (fi=Turun yliopisto|en=University of Turku|, 2018)
This study aimed at exploring Early Childhood teacher’s beliefs related to outdoor play and kindergarteners risk-taking behavior in a Finnish daycare. For that, interviews and observations were used. Interviews aimed in knowing how teachers understood a risk-taking behavior and their opinion about the importance and purpose of the outdoor time. Additionally, the observations were done by using an adapted rubric from Sandseter’s (2007) study were different risky categories were defined. Children in the present study seemed to seek risks by challenging their play and they involved in different levels of risk which was suitable for their individual acceptance of risk. During the 14 days of observation, children involved in different risky behaviors from which 8.38% were stopped by the adult. Which means 91.62% were not stopped. Overall, children engaged in risky situations around 501 times. The most stopped behavior was the bad use of are and the percentages of stopped and non-stopped behaviors varied from one day to another, some days the stopped behavior percentage was of 18.52% and others 0%. The main conclusion drawn from this study is that teachers and the environment play an important role in the use of the outdoor and on promoting opportunities for children to take risks.